Critical Estimation of Strength of Coating of Solvent Layer on the Basis of Adhesive Building Mixture - Loganina, V. I.; Zhegera, K. V. (New Ideas Concerning Science and Technology Vol. 7, 2021)
The article provides the information on the technique for estimating the strength of adhesion of a solution layer on the shear. The means for the strength of adhesion measuring, their metrological characteristics are proposed. The appearance and operation principle of the GT 2.2.3 device is described. A technique for assessing the strength of adhesion of tile adhesives to the shear using a GT 2.2.3 device is described. The information is given on the results of testing of an adhesive layer on the basis of a cement substrate. It is shown that the tensile stresses appearing in the adhesive layer are less than the tensile strength at shearing, and the shear strength exceeds the values of the maximum tangential stresses. The proposed technique for estimating the strength of adhesion to shear allows us to take into account not only the adhesion strength of adhesive adhesion to the substrate, but also the shear bond strength. Having such data it is possible to speak about the adhesion strength of the adhesive layer to the substrate.